Improving the diagnosis of acute pyelonephritis using Doppler ultrasound - Tokhirjonov Mukhammadjon; Yakubov Nodir; Zulunov Azizbek (Zien Journals, 2022)
This article describes the way of improving the diagnosis of cute pyelonephritis, which is a bacterial infection of the renal pelvis and parenchyma most commonly seen in young women. It remains common and continues to have significant morbidity in certain groups of patients, using doppleroghraphy
Keywords: Acute pyelonephritis; magnetic resonance; urinary tract infection; doppleroghraphy